Differential effects of work and socioeconomic status on breastfeeding duration in times of crisis - Chadia Haddad; Paula Hage Boutros; Hala Sacre; Rana Rizk; Cosette Fakih EL Khoury; Bahia Abdallah; Joanne Karam; Pascale Salameh (Discover Public Health)
Abstract Introduction This study aimed to examine the association between breastfeeding duration and breastfeeding attitudes, sociodemographic variables, lifestyle (diet, sleep, supplement intake, toxic habits), mental health, and employment. It assessed the differential results, stratifying the sample according to working and socioeconomic status. Methods A cross-sectional study was conducted among Lebanese mothers who have recently breastfed. Validated scales were used to assess the independent variables’ concepts. Descriptive, bivariable, multivariable, and stratified analyses were conducted. Results The median breastfeeding duration was 10 months (25th percentile: 4 months; 75th percentile: 18 months), while the median duration of exclusive breastfeeding was 6 months (25th percentile: 2 months; 75th percentile: 6 months). 45.6% of women breastfed for less than 6 months. The majority of women received breastfeeding support mainly from their partners (83.3%), followed by a family member (79.3%) or friends (69.5%). Additionally, 30.5% of participants fasted while breastfeeding their last child. Maternal fasting during breastfeeding, higher maternal education level, and favorable breastfeeding attitudes were significantly associated with longer breastfeeding duration. This association was stronger among low-income mothers, despite higher insomnia levels. Notably, stratification by employment did not show differences in associations’ magnitude. Conclusion This study highlighted the interrelationship of sociodemographic, cultural, psychological, and behavioral factors associated with breastfeeding duration among Lebanese mothers. Higher education, favorable breastfeeding attitude, and fasting during breastfeeding were the most important correlates with breastfeeding duration, particularly among women of lower socioeconomic status. Future studies with larger, more diverse populations and longitudinal designs are warranted to explore the causal relationships between these factors and breastfeeding duration.